DIGESTIBILITY OF RATIONS CONTAINING BREAD WASTED FERMENTED BY PROBIOTIC - D. N., Sembiring; Sudiastra, I W.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the feeding of rations containing bread wasted fermented probiotic broilers digestibility. This research was conducted at the Faculty of Animal Husbandry Farm, Udayana University Sesetan and Animal Nutrition Lab at Sudirman Campus, Denpasar. Bali. This study was conducted for 60 days, using a completely randomized design (CRD) consisting of 5 treatments and 4 replicates. Each cage was filled with 4 broilers with homogeneous body weight ranging from 51.07g ± 4.33g. The treatments consisted of R0 (100% commercial ration), R1 (90% commercial ration + 10% fermented bread waste flour), R2 (85% commercial ration + 15% fermented bread waste flour), R3 (80% commercial ration + 20% fermented bread waste flour). R4 (75% commercial ration + 25% fermented bakery waste flour). There were 5 variables observed, namely dry matter digestibility, organic matter digestibility, crude protein digestibility, crude fiber digestibility, crude fat digestibility. The results showed that the treatment of R2 had the highest value of each variable. The results of the analysis of variance showed that the use of probiotic fermented bread waste flour at the level of 0%, 10%, 15%, 20%, 25% in the ration gave an effect that was not significantly different (P>0.05) to the digestibility of the ration in broilers. The conclusion obtained in this study is that the provision of rations containing probiotic fermented bread waste at levels of 10%, 15%, 20%, and 25% does not affect the digestibility of dry matter, digestibility of organic matter, digestibility of crude protein, and digestibility of crude fat, but the provision of bread waste in rations at 20% and 25% shows significantly different results (P<0.05) lower and can reduce the digestibility of crude fiber.